Distributed Bragg Reflectors Employed in Sensors and Filters Based on Cavity-Mode Spectral-Domain Resonances - Michal Gryga; Dalibor Ciprian; Petr Hlubina (Sensors, 2022)
Spectral-domain resonances for cavities formed by two distributed Bragg reflectors (DBRs) were analyzed theoretically and experimentally. We model the reflectance and transmittance spectra of the cavity at the normal incidence of light when DBRs are represented by a one-dimensional photonic crystal (1DPhC) comprising six bilayers of TiO<semantics>2</semantics>/SiO<semantics>2</semantics> with a termination layer of TiO<semantics>2</semantics>. Using a new approach based on the reference reflectance, we model the reflectance ratio as a function of both the cavity thickness and its refractive index (RI) and show that narrow dips within the 1DPhC band gap can easily be resolved. We revealed that the sensitivity and figure of merit (FOM) are as high as 610 nm/RIU and 938 RIU<semantics>−1</semantics>, respectively. The transmittance spectra include narrow peaks within the 1DPhC band gap and their amplitude and spacing depend on the cavity’s thickness. We experimentally demonstrated the sensitivity to variations of relative humidity (RH) of moist air and FOM as high as 0.156 nm/%RH and 0.047 %RH<semantics>−1</semantics>, respectively. In addition, we show that, due to the transmittance spectra, the DBRs with air cavity can be employed as spectral filters, and this is demonstrated for two LED sources for which their spectra are filtered at wavelengths 680 nm and 780 nm, respectively, to widths as narrow as 2.3 nm. The DBR-based resonators, thus, represent an effective alternative to both sensors and optical filters, with advantages including the normal incidence of light and narrow-spectral-width resonances.